Review of Chalcovietnamicus Marusik, 1991, with description of four new species (Araneae, Salticidae, Euophryini) - Yu, Kun; Hoang, Quang Duy; Maddison, Wayne P.; Zhang, Junxia (Zootaxa, 2023)
The euophryine genus Chalcovietnamicus Marusik, 1991, a member of the Laufeia group of genera, is reviewed, and four new species from southern China and Southeast Asia are described with both sexes: Chalcovietnamicus logunovi Yu, Maddison & Zhang, sp. nov., C. marusiki Yu, Maddison & Zhang, sp. nov., C. terbakar Yu, Maddison & Zhang, sp. nov. and C. weihangi Yu & Zhang, sp. nov.. The monotypic genus Junxattus Prószyński & Deeleman-Reinhold, 2012 syn. nov. is considered as a junior synonym of Chalcovietnamicus Marusik, 1991, and Parvattus Zhang & Maddison, 2012 is revalidated and removed from synonymy with Chalcovietnamicus Marusik, 1991. The previously unknown female of C. vietnamensis (Żabka, 1985) is described based on specimens from Vietnam and Singapore. All species of Chalcovietnamicus are assigned to two species groups (daiqini-group and vietnamensis-group), except C. naga Logunov, 2020 that is herein considered as an incertae sedis.